Household food insecurity and physical activity behaviour in Ecuadorian children and adolescents: findings from the Ecuador 2018 National Health and Nutrition Survey (ENSANUT-2018) - Rishika Chakraborty; Rodrigo X Armijos; M Margaret Weigel (Cambridge University Press, 2024)
Abstract Objective: Ecuador has a high prevalence of household food insecurity (HFI) and is undergoing nutritional and epidemiologic transition. Evidence from high-income countries has reported negative or null associations between HFI and physical activity (PA) in children. It remains uncertain whether the same is true of those from low- and middle-income countries like Ecuador whose environmental and socio-demographic characteristics are distinct from those of high-income countries. We aimed to investigate the association of HFI with PA, sedentary behaviour (SB) and anthropometric indicators in children. Design: Cross-sectional analysis of data from the nationally representative 2018 Ecuadorian National Health and Nutrition Survey. Data were collected on HFI, PA, SB, socio-demographic characteristics and measured height and weight. Unadjusted and adjusted linear, log-binomial and multinomial logistic regression analyses assessed the relationship of HFI with PA, SB, stunting and BMI-for-age. Setting: Ecuador. Participants: 23 621 children aged 5-17 years. Results: Marginal and moderate-severe HFI was prevalent in 24 % and 20 % of the households, respectively. HFI was not associated with PA, SB, stunting nor underweight. Moderate-severe HFI was associated with a lower odds of overweight and obesity. However, adjustment for household assets attenuated this finding for overweight (adjusted OR:0·90, 95 % CI: 0·77, 1·05) and obesity (adjusted OR: 0·88, 95 % CI: 0·71, 1·08). Conclusion: HFI is a burden in Ecuadorian households, but is not associated with PA, SB nor anthropometric indicators in children aged 5-17 years. However, a concerning prevalence of insufficient PA was reported, emphasising the critical need for evidence-based interventions aimed at promoting PA and reducing SB.